2006
DOI: 10.1038/sj.emboj.7601199
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of myeloid lineage conversion using mice expressing an inducible form of C/EBPα

Abstract: CCAAT/enhancer-binding protein (C/EBP) a is a critical regulator for early myeloid differentiation. Although C/EBPa has been shown to convert B cells into myeloid lineage, precise roles of C/EBPa in various hematopoietic progenitors and stem cells still remain obscure. To examine the consequence of C/EBPa activation in various progenitors and to address the underlying mechanism of lineage conversion in detail, we established transgenic mice expressing a conditional form of C/EBPa. Using these mice, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 31 publications
2
47
0
Order By: Relevance
“…These observations mirror those from previous studies that showed that CEBPA has lineage switch potential when expressed in lymphoid cells. [43][44][45][46][47] Although the role of C/EBP␣ in lymphoid cell fate decision may not be fully understood yet, as highlighted by recent observations indicating that overexpression of C/EBP␣ due to chromosomal translocations may be involved in B-cell ALLs, 48,49 our studies show that decreased expression of C/EBP␣ in hematopoietic stem cells can be sufficient to induce T-cell transcripts.…”
Section: Discussionmentioning
confidence: 85%
“…These observations mirror those from previous studies that showed that CEBPA has lineage switch potential when expressed in lymphoid cells. [43][44][45][46][47] Although the role of C/EBP␣ in lymphoid cell fate decision may not be fully understood yet, as highlighted by recent observations indicating that overexpression of C/EBP␣ due to chromosomal translocations may be involved in B-cell ALLs, 48,49 our studies show that decreased expression of C/EBP␣ in hematopoietic stem cells can be sufficient to induce T-cell transcripts.…”
Section: Discussionmentioning
confidence: 85%
“…[53][54][55] Indeed, recent work has shown that ectopic C/EBP␣ expression can actually direct differentiation along the monocytic and not the predicted granulocytic lineage. [55][56][57][58] To resolve this conundrum, a recent study has demonstrated the importance of "secondary" cell-fate determinants, which are regulated by the primary determinant and act as counterantagonistic repressors; thus, secondary determinants such as Gfi1 and Egr1/Egr2 may be pivotal in tipping the balance between granulocytic and monocytic development, respectively. 36 Our results support a role of Mef2c as a secondary determinant in determining monocytic fate by simultaneously supporting the monocytic differentiation program and inhibiting granulopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…Use of a regulated C/EBPa transgene and lineage depletion only after transduction in this protocol minimizes biases due to lineage-specific cell cycle inhibition. Consistent with the conclusion that C/EBPa can direct monopoiesis as well as granulopoiesis, transduction of B-or T-cell progenitors with C/EBPa induces macrophage but not neutrophil development (Heavey et al, 2003;Xie and Graf, 2004;Laiosa et al, 2006); transplantation of mice with marrow transduced with C/EBPa increases the proportion of monocytes from 13 to 88%, while inhibiting erythropoiesis (Suh et al, 2006); and CLP or MEP isolated from mice expressing a C/EBPa-ER(T) transgene from the H2K promoter develop into macrophages upon exposure to 4-hydroxytamoxifen (Fukuchi et al, 2006). In contrast, C/EBPa-ER converts CD71…”
Section: Ccaat/enhancer-binding Protein a B And Ementioning
confidence: 99%